Peran Majelis Ulama Indonesia dalam Penetapan Fatwa DSN-MUI - Muchlis, Muchlis (Ecopreneur : Jurnal Ekonomi dan Bisnis Islam, 2023)
The fatwa council of the National Assembly of the Shari’ah Scholars Indonesia Many provide contribution of positive legal regulation against the law especially in the field of finance, business, economic and shariah fatwa as the answer to a problem that happesn sometimes also resulting from the musyawaran DSN itself where over shadowing the power of the law not only by the MUI but also set in the Ordinance so that results of the Indonesia bank of fatwa DSN-MUI can have the force of law that are binding in the economic development of the muslims through the sharia very many are that economic system and the role of the tribunal contribution scholars Indonesia with some effective system. Then to achieve the vision and mission of the Shar’a is very economic growth requered a fatwa issued by the DSN-MUI.Keywords: Fatwa, DSN-MUI, Ekonomi Syariah Abstrak Fatwa Dewan Syariah Nasional Majelis Ulama Indonesia telah banyak memberikan sumbangsih hukum terhadap regulasi hukum positif terutama dibidang keuangan, bisnis, dan ekonomi syariah, fatwa sebagai jawaban dari suatu permasalahan yang terjadi kadang pula juga dihasilkan dari musyawarah DSN itu sendiri di mana yang menaungi kekuatan hukum tidak hanya oleh MUI tetapi juga di atur dalam peraturan Bank Indonesia sehingga hasil fatwa DSN-MUI dapat mempunyai kekuatan hukum yang mengikat. Dalam perkembangan ekonomi umat melalui sistem ekonomi syariah sangat banyaklah sumbangsih serta peran dari Majelis Ulama Indonesia dengan beberapa sistem yang efektif. Maka untuk tercapainya visi misi utama dari pertumbuhan ekonomi syariah sangat dibutuhkan fatwa yang dikeluarkan oleh DSN-MUI.Kata Kunci: Fatwa, DSN-MUI, Ekonomi Syariah